2014
DOI: 10.1002/cphc.201402200
|View full text |Cite
|
Sign up to set email alerts
|

Stable Single‐Molecule Lines of Terrylene in Polycrystalline para‐Dichlorobenzene at 1.5 K

Abstract: The spectroscopic properties of single terrylene (Tr) molecules are studied in a polycrystalline matrix of para-dichlorobenzene (p-DCB) at 1.5 K. Samples grown in a glass capillary show a very strong site at 597 nm, which is redshifted by more than 700 cm(-1) from the observed transition energy for Tr in p-DCB prepared as a film on a coverslip (572 nm). Each of these two sites is characterized by measuring their single-molecule spectroscopic parameters at 1.5 K. Lifetime-limited linewidths of 45±5 MHz are foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…We observed linewidths on the order of the lifetime limit (lifetime limits of 26.5 MHz and 29.5 MHz were reported previously for the normal and red sites in anthracene respectively): for the normal site 50 % of the molecules have a homogeneous linewidth less than 29.0 MHz, for the red site the median is about 45.0 MHz. This is in line with the observations of near‐lifetime‐limited line widths for other fluorescent polyaromatic molecules like terrylene embedded in pDCB or oDCB …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We observed linewidths on the order of the lifetime limit (lifetime limits of 26.5 MHz and 29.5 MHz were reported previously for the normal and red sites in anthracene respectively): for the normal site 50 % of the molecules have a homogeneous linewidth less than 29.0 MHz, for the red site the median is about 45.0 MHz. This is in line with the observations of near‐lifetime‐limited line widths for other fluorescent polyaromatic molecules like terrylene embedded in pDCB or oDCB …”
Section: Discussionsupporting
confidence: 91%
“…There is a large energy splitting between the two sites of about 670 cm −1 . Similarly large splittings between sites were observed for terrylene in pDCB . For terrylene it was suggested that the redshift of the red site compared to the normal site is the result of an increased effective local pressure for the red site.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the mentioned studies, Tr molecules, optically excited to the S 1 state, were capable to emit more than 10 5 uorescence photons before It is well known that the rate of intersystem crossing transition increases in environments possessing heavyatoms [20], by the same talk, these media are responsible for quenching of the molecular uorescence. It was * corresponding author; e-mail: kozank@ifpan.edu.pl therefore surprising that Tr in polycrystalline ortho- [21] and para-dichlorobenzene [22], both host matrices with chlorine as the heavy-atoms, create bright and highly photostable single-molecule systems. Negligible role of the external heavy-atom eect on the Tr emission may be related to much higher triplet state depopulation rate than the rate of its population [6].…”
Section: Introductionmentioning
confidence: 99%
“…At cryogenic temperature and in suitable rigid matrixes, the absorption spectrum of a molecule presents an extremely narrow electronic transition that occurs without any creation or annihilation of phonons, and is therefore called the zerophonon line (ZPL). Its linewidth is chiefly determined by the lifetime of the excited state and lies in the range of 10-50 MHz for many well-studied host-guest systems [13][14][15][16][17][18][19]. Because of its sharpness, the ZPL is extremely sensitive to the molecule's local environment.…”
mentioning
confidence: 99%